A Mixed‐Anion System Consisting of a Germyl Anion and Anions Delocalized on Conjugated Carbon Ring Skeletons. Issue 25 (8th March 2019) - Fujimori, Shiori; Mizuhata, Yoshiyuki; Tokitoh, Norihiro
Abstract: A trianion consisting of one germyl anion and two anions delocalized on conjugated carbon ring skeletons was synthesized by trimerization of the germanium analogue of the anthryl anion, which exhibits high germylene character. In addition, the generation of the putative intermediate of this reaction, the radical anion of 9‐germaanthracene, was confirmed by the formation of the corresponding dimeric dianion. The isolated trianion and dianion were characterized by X‐ray crystallographic analysis together with NMR spectroscopy and theoretical calculations. Abstract : A mixed anion : A trianion consisting of one germyl anion and two anions delocalized on conjugated carbon ring skeletons was synthesized by trimerization of the germanium analogue of the anthryl anion, which exhibits high germylene character. In addition, a dianion, the dimer of the 9‐germaanthracene radical anion, having two germyl anions was isolated.